THE IMPORTANCE OF THE CONTROLLER. - Kester, R. B. (The Accounting Review, 1928)
Abstract The article presents information about the role of controller in a business organization. Qualifications and training of the controller may not be out of place. It seems that the primary requisite is that he shall be a business man. While he, of course, must be a skilled accountant that characteristic is secondary to the one just mentioned. Because of demands made on him in the making of records and drafting of reports which shall be usable by all operating executives, it is absolutely essential that he have a sound basic knowledge of all of the functional activities of the business. This means that he must have an understanding of the principal operating problems of the business. Without this he cannot adequately perform duties of his office. Because he is brought in such frequent contact with officials of the company, he must also be a student of men. Coming, as he does, into close relationship with all executives of the business he must know how to get along without undue friction with the men whom he is serving and whose activities it is his duty to control from an accounting standpoint, as distinct from an operating standpoint. It is thus seen that the controller must have a thorough training in business and this should give him a basic understanding of the broad movements of business, as well as a particularly intimate knowledge of the operation of his own business.